BRANKAS SYSTEM USING ANDROID BASED BARCODE SCANNER - Ismangil, Agus; Mulyati, Mulyati; Erniyati, Erniyati (JIPETIK:Jurnal Ilmiah Penelitian Teknologi Informasi & Komputer, 2020)
The use of a barcode scanner system on Android is applied to facilitate the user or users in accessing a system where in this system the barcode scanner serves as the initial key to accessing a safe. Research and evaluation results show that the use of QR Code (Quick Respone Code) can store numeric data types up to 7,089 characters, alphanumeric data up to 4,296 characters, binary codes up to 2,844 bytes and kanji letters up to 1,817 characters. QR Code is also resistant to damage, because QR can correct errors up to 30%, so the use of QR Code on a system can increase the speed of work and accuracy of detection on the system.